2003
DOI: 10.1046/j.1365-2516.2003.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial haemorrhage among a population of haemophilic patients in Brazil

Abstract: Intracranial haemorrhage (ICH) is a common cause of morbidity and mortality in haemophilic patients. The overall incidence of ICH has been reported to range from 2.2% to 7.5% in patients with haemophilia. From 1987 to 2001, 401 haemophilic patients from the Serviço de Hemofilia, Disciplina de Hematologia e Hemoterapia, Universidade Federal de São Paulo were evaluated. The episodes of ICH were documented by CT scan and the anatomic location, clinical presentation, relationship to trauma and clinical factors, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
79
3
11

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 15 publications
6
79
3
11
Order By: Relevance
“…In the present series, 3 (37.5 %, 3/8) developed neurological complications, including transient neurological abnormalities (blurred vision and dysarthria) and two patients achieved complete recovery from symptoms. Previous studies have shown variability in the incidence of long-term sequelae, ranging from 9.4 to 22.7 % [5,6,11,16]. This is also consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present series, 3 (37.5 %, 3/8) developed neurological complications, including transient neurological abnormalities (blurred vision and dysarthria) and two patients achieved complete recovery from symptoms. Previous studies have shown variability in the incidence of long-term sequelae, ranging from 9.4 to 22.7 % [5,6,11,16]. This is also consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…The mortality rate was 20.0 % (2/10) in our clinical series of patients. This is consistent with previous reports showing variability in mortality ranging from 0 to 25 % in patients with hemophilia presenting with ICH [5,6,11,16]. Two of our three patients who underwent neurosurgical intervention died, but this was likely the result of the ICH characteristics and patient conditions, not the neurosurgical intervention.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations